The Effect of Using Animation Movies on Students’ Listening Skill in Narrative Text at State Senior High School 3 Pekanbaru - Agus, Ahmadi Rahman; Syahputra, Idham (Journal of English and Arabic Language Teaching, 2023)
The Purpose of this research to find out whether or not there is significant effect of using Animation Movies on students’ listening skill in narrative text at State Senior High School 3 Pekanbaru. This research was pre-experimental design. The sample of this research was taken by purposive sampling. The population of this research was eleventh grade at Senior High School 3 Pekanbaru. The techniques of collecting data were multiple choice test. The researcher used statistical method of Non parametric Wilcoxon signed rank t-test by using SPSS Version 23 to analyzed the data. Based on data analysis of Wilcoxon formula. The sig value of Asymp. Sig (2-tailed) 0.000. it could be stated that 0.000<0.05, the value of 0.000 is lower than 0.05, it means null hypothesis (Ho) is rejected. While the alternative hypothesis (Ha) is accepted. So it can be concluded there is a significant difference of students listening skill in narrative text before and after being taught using animation movies.